Infectious respiratory tract disease in the dairy cattle’s in communal farming and their association to the Breeding of Pigeons in the Farm - Bzour, Mahyoub Izzat; Jodeh, Shehdeh; Mispan, Muhamad Shakirin (International Journal of Psychosocial Rehabilitation, 2020)
The infectious respiratory disease is one of the serious problems causing lower yield of cattle’s production. A study was undertaken in May 2018 to understand the knowledge of cattle’s farmers about breeding of pigeons in the farm. The specific objectives of the study were to establish what cattle’s farmers know about infectious respiratory tract disease, evaluate the cattle health problem related infectious respiratory disease, examine farmers’ practices in managing cattle’s disease, and recommend policies on disease management based on the results of the study. Results showed that 85.7% from the tested farm are closed crowded, 67.9% of the respondent farmers breed pigeons in the farm with animals, in addition, the number of animal death annually related respiratory disease reach to 10 to 20 animals. Our study suggests that there is a need to increase awareness about infectious respiratory diseaseamong Palestinians farmers.